Evolution and future of health psychology - Garzón, Adela; Caro, Isabel (Anales de Psicología / Annals of Psychology, 2013)
This paper addresses the development of new plans of integration, with the aim of undertaking a critical review of the present status of health psychology. We emphasize that health psychology has overcome its growing stage when the risk of stagnation and a consequent loss of relevance and social projection existed. During its period of professionalization there was a spreading and proliferation of approaches due more to external reasons than to reflection within the field. Today the central issue, in many countries relates to the integration of health policies through collective and global actions. Health psychology professionals should move away from the traditional academic and scientific traditions and be closer to the current health realities and to the international plans that globalization demands.